Single agent lenalidomide activity in multiple myeloma relapse evidenced uniquely by CT/PET - Alessandro Gozzetti; Vania Rossi; Alfonso Cerase; Giulia Papini; Marzia Defina; Monica Bocchia (Mediterranean Journal of Hematology and Infectious Diseases)
A 71 year old female with multiple myeloma presented with back pain seven year after autologous stem cell transplant. Skeletal bone survey and magnetic resonance imaging did not show a relapse that was evidenced by CT/PET. Lenalidomide as single agent induced a complete disappearance of the lesions 6 months later and confirmed after one year at CT/PET.